To find her place - Mason, Susan Anne (Mason, Susan Anne. Redemption's light, 2021)
"In the midst of WWII, Jane Linder pours all of her dreams for a family into her career at the Toronto Children's Aid Society. Garrett Wilder has been hired to overhaul operations at the society and hopes to earn the vacant director's position. But when feelings begin to blossom and they come to a crossroads, can they discern the path to true happiness?"--